KELAYAKAN PENGGUNAAN MEDIA VIRTUAL REALITY DALAM MELATIH SISWA MEINGKATKAN KETERAMPILAN MENGIDENTIFIKASI PERUBAHAN PADA PEMBELAJARAN SEJARAH - Fini Fajri Mulyani; Ofianto Ofianto (Jurnal Kronologi, 2022)
Thinking skills to identify changes in historical events is one part of historical thinking skills that must be possessed by students. One of the ways to improve change thinking skills is by using interactive media. Therefore, this study aims to (1) determine whether the use of Virtual Reality (VR) media can improve students' skills in identifying changes in historical events, (2) determine the feasibility and practicality of Virtual Reality (VR) media in improving students' skills in identifying changes in historical events, (3) knowing the effectiveness of using Virtual Reality (VR) in improving students' skills in identifying changes in historical events. This research method is Research and Development (R&D) using the Thiagarajan 4D development model consisting of 3 stages of development, namely defining, planning (design), and developing (develop). The results showed that (1) the feasibility of virtual reality media in general was in the very feasible category and was able to improve thinking skills in identifying changes in historical events, (2) the practicality of virtual reality media as a whole was in the very practical category. Keywords: interactive learning media, virtual reality, change thinking skills, historical thinking